Coastal marine steel corrosion: the environment’s influence and in-situ monitoring – A review - Onoufriou, Toula (My University, 2023)
It is without doubt that marine corrosion is of great interest and significance from various viewpoints, starting from an engineering design point of view, as safety concern view but also from an economic standpoint. At the forefront of exposure, coastal marine steel structures are exposed to the sea environment either directly in an immersed setting or in the immediate vicinity of the marine atmosphere (mid-laden sea air). Offering its contribution to understanding corrosion, this study gathers the literature’s available findings in an effort to extract, in a concise and refined manner, the knowledge on the marine environment’s effect on steel structures and the field monitoring of the corrosion taking place as a result of these interactions. Ultimately, it is expected that this study will form a reliable basis for further research, to be used in anticipating a realistic marine corrosion rate which will aid in avoiding over-engineering practices and properly appraising the remaining life of existing infrastructure.